Earthquake intensity for Lalitpur, Nepal - Parajuli , Hari Ram; Thapa, Milan (Journal of Innovations in Engineering Education, 2025)
Using probabilistic seismic hazard analysis (PSHA), an effort has been made to evaluate the seismic hazard at rock level in terms of peak horizontal acceleration (PHA) at two locations in the Lalitpur district. The site's earthquake database was created by combining the several databases. To depict the region's earthquake recurrences, a magnitude frequency relationship was created. The probabilistic spectra for the two sites were then generated by estimating the peak ground acceleration using Young's et al. 1997 attenuation relation. The findings indicate that there is a greater degree of seismic risk in the locations that support the current design guidelines for earthquake resistance.